Eikenella corrodens Sepsis with Cerebrospinal Fluid Pleocytosis in a Very Low Birth Weight Neonate - Christopher Sawyer; Dimitrios Angelis; Robert Bennett (Case Reports in Pediatrics)
We report a case of Eikenella corrodens sepsis associated with CSF pleocytosis in a very low birth weight neonate. A 1000-gram male neonate was born at 27-week gestation due to preterm labor. The patient presented with signs and symptoms of sepsis and was treated for suspected meningitis with intravenous ampicillin and gentamicin for 7 days, with cefotaxime added for three weeks. He had a normal brain MRI at discharge and normal development at 6 months of life. To our knowledge, this is the first case of E. corrodens sepsis and associated meningitis in a very low birth weight neonate.